Peran Perempuan Buruh Tani Rumput Laut Terhadap Pendapatan Keluarga di Desa Liya Onemelangka Kabupaten Wakatobi Menurut Ekonomi Syariah - Marliyani, Marliyani; Puspita Sari, Sarni Handayani (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
This study aims to examine the role of women as seaweed farm laborers in increasing household income in Liya Onemelangka Village, Wakatobi Regency, from an Islamic economic perspective. This research uses a qualitative approach with data collection techniques such as observation, interviews, and documentation. The findings reveal that women perform dual roles as housewives and income earners. Their skills in seaweed seedling and cultivation contribute significantly to family income, especially amid limited economic conditions. From the perspective of Islamic economics, these active roles reflect the values of justice, hard work, and social responsibility as mandated in the Qur’an Surah An-Nahl verse 97. These results highlight the importance of recognizing women’s economic contributions and the need for inclusive development based on Islamic values.